(untitled) (Numerus academy review, 2026)
The preamble to the Algerian constitution enshrined the principle of the constitution supremacy, and the constitutional amendment created a constitutional court with jurisdiction over constitutional oversight, in addition to other constitutional competencies that would protect the state’s legal system. This amendment strengthened the jurisdiction of this court to control the constitutionality of treaties, by controlling the compatibility of laws and regulations with treaties, which is devoted to the protection of the supremacy of the Constitution over international rules, and the superiority of treaties over domestic laws. But, to achieve this purpose, the ambiguity must be lifted over the constitutional texts related to the field of these two controls and the implications for them, as a guarantee for activating the role of the Constitutional Court in establishing the rank of treaties within the hierarchy of legal rules.